Patient Preferences and Values in Decision Making for Migraines: A Systematic Literature Review - Xianpeng Xu; Qingjie Ji; Min Shen (Pain Research and Management)
Objective. To comprehensively summarize the evidence on the preferences and values of migraine patients. Methods. We searched PubMed, Embase, Web of Science, China National Knowledge Infrastructure, Sino-Med, Chongqing VIP, and Wanfang Data for studies on the preferences and values of migraine patients. A qualitative review was performed, but no quantitative synthesis. Results. Twenty‐one studies were finally included, involving a total of 8701 participants. Patients expected a cure, to be symptom-free, a reduction in frequency of headaches, a reduction in severity of headaches, and an improved quality of life from their preventive treatment. Patients expected rapid pain relief, complete pain relief, return to normal activities, no recurrence, and no adverse events from their acute symptomatic treatment. Conclusion. Efficacy is the primary consideration in the treatment of migraine. Specifically, the most important embodiment of patient preferences and values is the reduced frequency of attacks with preventive treatment as well as prompt analgesia with acute symptomatic treatment.